Quality of life as an outcome variable in the management of advanced cancer - Bisht Manisha; Bist S; Dhasmana D; Saini Sunil (Indian Journal of Medical and Paediatric Oncology)
Background and Objective: Though well recognized in the West, palliative care and quality of life are relatively newer concepts in a developing country like India. The aim of this study was to assess the effect of palliative care on pain and quality of life and to identify the association between the two. Study Design: Observational prospective study. Materials and Methods: Patients with advanced cancer, receiving palliative drug therapy, were recruited from a tertiary care hospital. City of Hope Medical Center Quality of Life Survey and visual analog scale (VAS) were used to assess the quality of life and cancer pain severity, respectively. Results: A total of 100 patients were included in the study. Palliative drug therapy produced a significant reduction in pain scores expressed as mean±SD in VAS [7.13±2.2 vs. 2.62±2.1 (P<0.001) after 1 month in 93 patients; 7.06±2.1 vs. 2.47±2.1 (P<0.001) after 1 month and 2.02±1.9 (P<0.001) after 2 months in 51 patients]. Also, significant improvement in the quality of life scores [919.78±271.3 vs. 1280.65±306.8 (P<0.01) after 1 month in 93 patients; 950.39±238.2 vs. 1336.67±291 (P<0.01) after 1 month and 1405.49±368.3 (P<0.01) after 2 months in 51 patients] was obtained. There was a high correlation between the average change of pain intensity and quality of life scores (r=−0.53, P<0.02). Overall, a reduction in pain resulted in significant improvement in the quality of life (P<0.001). Conclusion: This study emphasizes the role of palliative care and, more importantly, pain management in improving the quality of life of advanced cancer patients.